Evidência de um sistema de alarme de sufocamento na matéria cinzenta periaquedural dorsal do rato: efeitos do isolamento neonatal e de tratamentos panicolíticos clinicamente eficazes com clonazepam e fluoxetina - Schimitel, Fagna Giacomin (2014)
Dyspnoea, ‘hunger for air’ and urge to flee are the cardinal symptoms of respiratory-type panic attacks. Patients also show baseline respiratory abnormalities and a higher rate of comorbid and antecedent respiratory diseases. Panic attacks are also precipitated by both the infusion of 0.5 M sodium lactate and the inhalation of 5-7% CO2 in predisposed patients but not in healthy volunteers or patients without panic disorder. Further studies showed that panic patients are also hyperresponsive to hypoxia. These and other observations led Klein (Arch Gen Psychiat, 50: 306, 1993) to suggest that clinical panic is the misfiring of a suffocation alarm system. In rats, cytotoxic hypoxia of chemoreceptor cells by intravenous injections of potassium cyanide (KCN) produces short-lasting flight behaviors reminiscent of panic attacks. KCN-induced flight behaviors are blocked both by denervation of chemoreceptor cells and lesion of dorsal periaqueductal gray matter, a likely substrate of panic, given that the defensive behaviors produced by stimulation of dorsal periaqueductal gray matter have been proposed as models of panic attack. Clinical data also suggest that separation anxiety in childhood and major depression predispose to panic disorder. Therefore, this study analyzed the duration of escape behavior produced by KCN after acute and chronic treatment with clonazepam (0.01-0.3 mg / kg, ip) and fluoxetine (1-4 mg / kg / day / 21 days, ip), respectively in intact rats. In addition to checking the behavior effects of CO2 and KCN, either alone or combined with dorsal periaqueductal gray matter stimulation of male and female who suffered isolation neonatal rats. In male rats, the isolation caused significant reductions in median thresholds of galloping and urination. In general, ovariectomized showed greater than those of males, isolated or not isolated thresholds. Already CO2, produced 6 dose-dependent increases in responses median of immobility, exophthalmos, trotting, galloping and jumping thresholds. However, females rats were less sensitive to these effects. In relation to panicolitics, it was observed that the behaviors of escape produced by KCN are both attenuated by acute treatment with clonazepam and by chronic treatment with fluoxetine. These results support the involvement of MCPAd on a suffocation alarm mechanism